Formal Subdivision of the Holocene Series/Epoch - Walker, M. J. C.; Gibbard, P. L.; Berkelhammer, M.; Björck, Svante; Cwynar, L. C.; Fisher, D. A.; Long, A. J.; Lowe, J. J.; Newnham, R. M.; Rasmussen, S. O.; Weiss, H. (Springer, 2014)
This proposal, by a Working Group of Integration of ice-core, marine, and terrestrial records (INTIMATE) and the Subcommission on Quaternary Stratigraphy (SQS) of the International Commission on Stratigraphy (ICS), is for a formal subdivision of the Holocene Series/Epoch. Although previous attempts to subdivide the Holocene have proved inconclusive, recent developments in Quaternary stratigraphy, notably the definition of the Pleistocene-Holocene boundary and the emergence of formal subdivisions of the Pleistocene Series/Epoch, mean that it may be timely to revisit this matter. The Quaternary literature reveals a widespread but variable informal usage of a tripartite division of the Holocene ("early", "middle" or "mid-", and "late"), and we propose that this de facto subdivision should now be formalised to ensure consistency in stratigraphic terminology. We advocate a formal Early-Middle Holocene boundary at 8200 a BP and a formal Middle-Late Holocene boundary at 4200 a BP, each of which is linked to a Global Stratotype Section and Point (GSSP).